Infection Control Practices: Awareness and Knowledge of Undergraduates in Tertiary Care Hospital - Shah, Manali Hitenbhai; Shah, Latika Nitin (Annals of Pathology and Laboratory Medicine, 2019)
Background: Hospital acquired infection an infection occurring in a patient in a hospital or other health care facility in whom the infection was not present or incubating at the time of admission. Every person associated with health care work should have proper training, knowledge and practice for the same. Undergraduates do not have proper knowledge towards the health care management. As they are in the learning phase, need to train enough. Methods: It was an observational analytical study. 2nd year MBBS students were included in the study. A semi-structured preformed questionnaire of total 21 questions having multiple choice questions with the use of Google doc application. Data were analyzed by using Microsoft Excel program. Result: Total 143 2nd year MBBS students responded. Knowledge regarding needle stick injuries was 40-60 % while about MDR and XDR TB was up to 70-80 %. Around 60 % knew the correct dosage schedule of Hepatitis B vaccine whereas 70 % emphasized the importance of hand hygiene in hospital acquired infections. Conclusion: The study shows lack of knowledge and awareness amongst medical students about hospital acquired infections. There is to educate them enough by means of various curriculum activities. More such studies should be done in future to assess their KAP score and guide them well.